Work-life balance, perceived stress, & locus of control - Karkoulian, Silva (2014)
This study aims at verifying whether a lower level of perceived stress combined with a high level of control predict a higher level of perceived work life balance for employees in the Lebanese banking sector. Primary data was collected using 195 surveys that were distributed in several commercial banks in Lebanon. Correlations and regression were performed to test the suggested hypotheses. According to the result of this study, work life balance is positively affected by an increased level of control as well as a decreased level of perceived stress. Thus, organizations should make sure that their employees are experiencing a “fair” level of work life balance to ensure a maximized level of job performance, job satisfaction, and maximum organizational efficiency and productivity. Moreover, locus of control should be taken into consideration during the screening process of potential employees. Further research should concentrate more on women with an internal locus of control, on employees in other work sectors in Lebanon, on men working in banks, and on the role that employees’ work involvement and commitment levels play in affecting their perceived levels of stress and work life balance.